2014
DOI: 10.1128/aem.04233-13
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Identifies Epidemic Clones of Flavobacterium psychrophilum in Nordic Countries

Abstract: f Flavobacterium psychrophilum is the causative agent of bacterial cold water disease (BCWD), which affects a variety of freshwater-reared salmonid species. A large-scale study was performed to investigate the genetic diversity of F. psychrophilum in the four Nordic countries: Denmark, Finland, Norway, and Sweden. Multilocus sequence typing of 560 geographically and temporally disparate F. psychrophilum isolates collected from various sources between 1983 and 2012 revealed 81 different sequence types (STs) bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
72
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 31 publications
8
72
0
Order By: Relevance
“…For example, the founding and subfounding genotypes of CC-ST10 (i.e., ST2 and ST10) caused severe disease outbreaks in Europe and Chile and were proposed to have given rise to multiple highly pathogenic sublineages (28,(31)(32)(33). The findings of this study support this hypothesis, as all but 2 CC-ST10 isolates recovered in the United States were isolated from rainbow trout undergoing clinical BCWD.…”
Section: Discussionsupporting
confidence: 78%
See 4 more Smart Citations
“…For example, the founding and subfounding genotypes of CC-ST10 (i.e., ST2 and ST10) caused severe disease outbreaks in Europe and Chile and were proposed to have given rise to multiple highly pathogenic sublineages (28,(31)(32)(33). The findings of this study support this hypothesis, as all but 2 CC-ST10 isolates recovered in the United States were isolated from rainbow trout undergoing clinical BCWD.…”
Section: Discussionsupporting
confidence: 78%
“…Van Vliet et al (19,29,32), and the findings from this study suggest that the same may be true for some genotypes found in the United States (Table 2). For example, isolates belonging to CC-ST10 were recovered exclusively from rainbow trout, thus supporting the hypothesis that CC-ST10 strains are particularly adapted to this species, which is highly susceptible to BCWD, or its rearing conditions (32).…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations